Quality of Underground Water in the West Bank and its Suitability for Irrigation - M. S. Ali Shtayeh; Nihayeh Abu Hijleh (My University, 1994)
Chemical analysis was carried out on underground water samples taken from 192 wells, distributed throughout the West Bank of Jordan. The samples were collected twice; in 1982 and 1987. Water samples were classified on the basis of their salinity, sodium concentration, salinity hazard - sodium hazard, and suitability for irrigation. Water samples from different wells in different localities differed largely in their qualities. The results also showed a decline with time in water quality in the samples examined, especially in Jericho and the Jordan valley. The implications of the results on agriculture in the West Bank are also discussed.
نوعية المياه الجوفية في الضفة الغربية وصلاحيتها للري